Preparation and application of light-responsive mesoporous silica adsorption material

CN122937757APending Publication Date: 2026-10-20JILIN AGRICULTURAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611442685.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]基于现有技术存在的技术问题,本发明目的在于提供一种光响应介孔二氧化硅材料的制备方法,该方法制备出兼对三唑类物质具有高选择性、高光响应效率与良好循环稳定性的光响应介孔二氧化硅吸附材料,解决现有技术中选择性与光响应效率难以兼顾的技术矛盾

Benefits of technology

本发明中通过在羟基活化的介孔二氧化硅载体表面均匀相邻接枝,有效解决了现有光响应吸附材料选择性差、选择性提升与光响应效率难以兼顾、功能基团接枝不均的技术问题,有效提高了吸附材料对三唑类物质的吸附选择性,吸附效率显著提高,最大吸附量达到123.742mg/g,吸脱附循环稳定性也得到了明显的提升,经过10次连续吸附-脱附循环后,材料的可逆吸脱附吸附性能保持在90%以上,具有优异的光调控可逆性与循环复用稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the preparation and application of a photoresponsive mesoporous silica adsorbent material, belonging to the field of separation and adsorption material preparation technology. It involves preparing mesoporous silica (MS) using CTAB as a template, followed by hydroxyl activation to obtain MS-OH. A photoresponsive molecular intermediate, AB-TPI, is synthesized by reacting 3-(triethoxysilyl)propyl isocyanate and 4-aminoazobenzene. MS-OH, AB-TPI, and UPTES are then mixed and reacted to obtain the photoresponsive mesoporous silica adsorbent material. This invention effectively solves the technical problems of poor selectivity and the difficulty in simultaneously improving selectivity and photoresponsive efficiency in photoresponsive adsorbent materials. It improves the adsorption selectivity of the adsorbent material for triazoles, significantly increasing the adsorption efficiency, with a maximum adsorption capacity reaching 123.742 mg / g. After 10 consecutive adsorption-desorption cycles, the reversible adsorption-desorption performance of the material remains above 90%, exhibiting excellent photo-regulated reversibility and cyclic reuse stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of separation and adsorption material preparation technology, specifically to the preparation and application of a photoresponsive mesoporous silica adsorption material. Background Technology

[0002] Since the widespread application of chemical pesticides, they have played a crucial role in ensuring healthy crop growth, improving agricultural productivity, and stabilizing global food supplies. Among them, triazole pesticides, as a class of highly effective broad-spectrum fungicides, are widely used in agricultural disease control systems and have irreplaceable application value in crop protection. However, due to the high chemical stability and poor biodegradability of triazole compounds, they are difficult to degrade naturally in aquatic environments. They easily enter water bodies through surface runoff and persist for a long time, migrating and accumulating in aquatic ecosystems. They can not only accumulate in aquatic organisms but also enter humans through the food chain and drinking water. Even under low-concentration exposure conditions, they can still produce various potential toxic effects on organisms, including endocrine disruption, developmental abnormalities, and organ dysfunction, posing a continuous threat to ecological safety and human health. Therefore, developing efficient, stable, and environmentally friendly water removal technologies to effectively control triazole pesticide residues is of great significance for ensuring water environment safety and ecosystem health.

[0003] Adsorption technology has certain advantages in the removal of organic pollutants from water bodies due to its simple operation, mild conditions, and lack of secondary pollution. Mesoporous silica materials (MSNs) have attracted widespread attention in the field of adsorption and separation of organic pollutants in water bodies due to their highly ordered pore structure, large specific surface area, and good chemical stability. Among them, photoresponsive mesoporous silica has advantages such as adsorption-desorption cycle regeneration through light irradiation. However, in the targeted adsorption application of triazole pesticides, this type of material has gradually revealed significant technical shortcomings, making it difficult to simultaneously meet the dual requirements of high selective enrichment and efficient photocontrolled regeneration in complex water bodies. Existing photoresponsive mesoporous silica has poor adsorption specificity for triazole pesticides, resulting in low target enrichment efficiency and poor selectivity in complex matrices. Furthermore, the inherent kinetic limitations of conventional post-grafting processes, uneven distribution of photoresponsive groups, and difficulty in improving photocontrolled switching efficiency further hinder its effectiveness. Moreover, the above two problems have a clear trade-off relationship within the existing technological framework, making it difficult to solve them effectively at the same time. Introducing large-sized specific recognition groups to improve adsorption selectivity would further increase the steric hindrance of functional molecules, exacerbating pore blockage and uneven distribution during grafting, leading to a further decrease in photoresponse switching efficiency. Conversely, using pore expansion or multiple grafting processes to improve grafting uniformity typically comes at the cost of sacrificing specific surface area, increasing process complexity and preparation costs, and failing to simultaneously improve adsorption selectivity. Existing technologies mostly optimize only a single problem and have not yet formed a systematic solution that can simultaneously achieve targeted selective adsorption of triazoles and high photoresponse switching efficiency, thus limiting the practical application performance and application scope expansion of such materials. Summary of the Invention

[0004] Based on the technical problems existing in the prior art, the purpose of this invention is to provide a method for preparing photoresponsive mesoporous silica materials. This method prepares photoresponsive mesoporous silica adsorbent materials that have high selectivity, high photoresponse efficiency and good cycle stability for triazole substances, thus solving the technical contradiction in the prior art where selectivity and photoresponse efficiency are difficult to balance.

[0005] Another object of the present invention is to provide the application of the photoresponsive mesoporous silica material prepared by the above method.

[0006] The objective of this invention is achieved through the following technical solution: A method for preparing a photoresponsive mesoporous silica material includes the following steps: S1. Mesoporous silica MS was prepared by sol-gel method using hexadecyltrimethylammonium bromide (CTAB) as template, and then activated with hydroxyl groups to obtain MS-OH; S2. The photoresponsive molecular intermediate AB-TPI was synthesized by reacting 3-(triethoxysilyl)propyl isocyanate and 4-aminoazobenzene. S3. MS-OH, AB-TPI and γ-ureapropyltriethoxysilane (UPTES) are mixed and reacted to obtain the photoresponsive mesoporous silica adsorbent material MS-AZO-Urea.

[0007] Further, the preparation of mesoporous silica involves dissolving hexadecyltrimethylammonium bromide (CTAB) in a mixed solvent of sodium hydroxide aqueous solution and deionized water, adjusting the pH of the system to 11.5-12.5 to form a homogeneous mixed solution, then adding tetraethyl orthosilicate (TEOS), and reacting for 1.5-2.5 hours to obtain a white colloidal suspension. After the reaction, the product is collected by centrifugation, washed with deionized water and methanol, and dried to obtain a mesoporous silica precursor containing a template agent. The mesoporous silica precursor containing the template agent is dispersed in a mixed system of methanol and hydrochloric acid solution, and the template agent is removed by reflux. After the reaction, the solid product is collected by centrifugation and washed until neutral to obtain the mesoporous silica support MS.

[0008] Furthermore, the volume ratio of sodium hydroxide solution to deionized water in the mixed solvent is 1:150~160, the concentration of sodium hydroxide solution is 1.5~2.5mol / L, the mass ratio of CTAB to the mixed solvent is 1:475~485 g / mL, and the volume ratio of TEOS to the mixed solution is 1:95~98.

[0009] Furthermore, the reflux reaction temperature is 55~65℃, the reaction time is 10~12 h, the volume ratio of methanol to hydrochloric acid solution is 100:0.8~1.2, and the HCl concentration in the hydrochloric acid solution is 0.8~1.2 mol / L.

[0010] Furthermore, the hydroxyl activation involves dispersing MS in a dilute nitric acid solution to carry out the activation reaction. After the reaction is complete, the solid is collected by centrifugation, washed with deionized water until the filtrate is neutral, and dried to obtain the hydroxyl-activated mesoporous silica support MS-OH.

[0011] Furthermore, the activation reaction is carried out at a temperature of 75-85°C, for a reaction time of 3.5-4.5 h, with a concentration of 0.5 mol / L for dilute nitric acid, and the solid-liquid ratio of MS to dilute nitric acid is 1:75-85 g / mL.

[0012] A method for preparing a photoresponsive mesoporous silica material includes the following steps: S1. Preparation of hydroxyl-activated mesoporous dioxide support (1) Dissolve hexadecyltrimethylammonium bromide (CTAB) in a mixed solvent of sodium hydroxide aqueous solution and deionized water, adjust the pH of the system to 11.5~12.5 to form a homogeneous mixed solution, heat to 75~85℃ with stirring at 450~550 rpm, then add tetraethyl orthosilicate (TEOS), and continue stirring for 1.5~2.5 h to react and obtain a white colloidal suspension. After the reaction is completed, collect the product by centrifugation, wash with deionized water and methanol and dry to obtain a mesoporous silica precursor containing a template agent. The volume ratio of sodium hydroxide solution to deionized water in the mixed solvent is 1:150~160, the concentration of sodium hydroxide solution is 1.5~2.5 mol / L, the mass ratio of CTAB to the mixed solvent is 1:475~485 g / mL, and the volume ratio of TEOS to the mixed solution is 1:95~98. (2) The mesoporous silica precursor containing the template agent was dispersed in a mixture of methanol and hydrochloric acid solution with a solid-liquid ratio of 1:90~100 g / mL. The mixture was refluxed at 55~65℃ for 10~12 h to remove the template agent. After the reaction was completed, the solid product was collected by centrifugation and washed with methanol until neutral to obtain the mesoporous silica support MS. The volume ratio of methanol to hydrochloric acid solution was 100:0.8~1.2. The HCl concentration in the hydrochloric acid solution was 0.8~1.2 mol / L. (3) Disperse MS in 0.5 mol / L dilute nitric acid solution with a solid-liquid ratio of 1:75~85 g / mL, stir and reflux at 80℃ for 3.5~4.5 h to activate the surface hydroxyl groups, collect the solid by centrifugation after the reaction is completed, wash with deionized water until the filtrate is neutral, and dry to obtain hydroxyl-activated mesoporous silica support MS-OH; S2. Synthesis of AB-TPI 3-(triethoxysilyl)propyl isocyanate and 4-aminoazobenzene were dissolved in anhydrous tetrahydrofuran at a solid-liquid ratio of 7:22~26 g / mL. The reaction was carried out under reflux at 60~68℃ for 20~24 h in the dark and under nitrogen protection. After the reaction was completed, n-hexane was added and crystallization was carried out at -20℃ for 10~12 h. The precipitated product was washed and dried under vacuum to obtain the photoresponsive molecular intermediate AB-TPI. The mass ratio of 3-(triethoxysilyl)propyl isocyanate to 4-aminoazobenzene and n-hexane was 4~5:3. S3. The hydroxyl-activated mesoporous silica support MS-OH prepared in step S1 is dispersed in anhydrous toluene, and a mixture of AB-TPI and γ-ureapropyltriethoxysilane (UPTES) prepared in step S2 is added. The mixture is refluxed at 75-85°C for 10-12 h under light protection and nitrogen protection. After the reaction is completed, the product is collected by filtration, and unreacted monomers are removed by washing with methanol. Finally, the product is vacuum dried at 55-65°C for 12 h to obtain the photoresponsive mesoporous silica adsorbent MS-AZO-Urea. The solid-liquid ratio of MS-OH to toluene is 1:90-100 g / mL; the total amount of AB-TPI and UPTES is in a mass ratio of 1:8-10 to MS, and the mass ratio of AB-TPI to UPTES is 1-1.2:1.

[0013] This invention utilizes a synergistic process of hydroxyl-activated mesoporous silica support and bissilane co-grafting to construct a composite adsorption interface on the surface of hydroxyl-activated mesoporous silica, featuring a synergistic interaction of "photoresponse regulation unit + directional recognition unit." This systematically addresses the technical problems of poor selectivity, difficulty in balancing selectivity enhancement and photoresponse efficiency, and uneven grafting of functional groups in existing photoresponsive adsorption materials. Hydroxyl activation significantly increases the density and accessibility of reactive silanol groups on the mesoporous silica surface, providing ample and uniform reaction sites for the two silanes. Furthermore, the reactivity of AB-TPI and UPTES is similar to their molecular size, achieving synchronous and uniform grafting on uniform silanol sites. This ensures the proximity and uniform distribution of the two functional groups at the nanoscale, providing a structural basis for synergistic anchoring at two sites.

[0014] Azobenzene photoresponsive intermediate (AB-TPI) and ureapropyltriethoxysilane (UPTES) are uniformly grafted onto the surface of mesoporous silica via covalent bonds. Through the dual effects of local binding microenvironment regulation and interfacial dispersion enhancement, hydrogen bond recognition sites are introduced to improve selectivity while maintaining or even optimizing the photoresponsive switching efficiency of the material. This alleviates the problem that enhanced target recognition may lead to excessive binding, which would be detrimental to photocontrolled desorption. Increasing hydrogen bond recognition enhances adsorption binding force, leading to incomplete photocontrolled desorption and decreased switching efficiency. Maintaining high photoresponse efficiency, however, prevents targeted recognition, making simultaneous optimization difficult. This invention introduces urea groups, which form a uniform, adjacent distribution with azobenzene on the support surface. Because azobenzene is extremely sensitive to the polarity of its local microenvironment, its molecular geometry, dipole characteristics, and spatial occupancy change during photoinduced cis-trans isomerization. When the urea group recognition site is within a suitable spatial proximity to AB-TPI, this conformational change alters the local microenvironment, steric hindrance, and accessibility of the target molecule around the urea group. This modulates the probability and stability of hydrogen bond formation between the urea group and the target molecule, thereby increasing the difference in target molecule binding capacity under different photosteady states. This provides a basis for the synergistic regulation of selective adsorption and photocontrolled desorption.

[0015] When grafted with a single azobenzene silane, strong intermolecular hydrophobic interactions lead to aggregation and stacking on the silicon surface. The aggregated azobenzene molecules exhibit high steric hindrance, resulting in low cis-trans isomerization conversion rates. A large number of azobenzene molecules fail to complete conformational inversion, leading to a very low proportion of effective photoresponsive sites and a reduced apparent on / off ratio. Introducing UPTES co-grafting reduces the probability of high surface density AB-TPI arrangement in localized areas on the silanol-activated mesoporous silica surface. This allows for the coexistence of the two functional units on the surface. The polarity of the urea groups disrupts the hydrophobic aggregation of azobenzene, increasing the dispersion of AB-TPI at the interface and reducing its local aggregation. Monodisperse azobenzene exhibits low steric hindrance, improved isomerization conversion rates, and a significant increase in the number of effective photoresponsive sites.

[0016] For the target compound of this invention, which combines an aromatic hydrophobic structure with a nitrogen-containing triazole heterocycle, when the two types of functional units are in a suitable spatial proximity, different structural regions of the same triazole molecule can interact with AB-TPI and UPTES respectively, thereby obtaining multi-point synergistic binding gain (the benzene ring and azobenzene undergo π-π stacking, and the triazole ring and adjacent urea groups form hydrogen bond interactions). For aromatic interfering substances that lack matching hydrogen bond interaction sites with urea groups, or whose hydrogen bond site spatial configuration does not match the composite interface, their interaction with the material mainly relies on non-specific hydrophobic interactions and π-related interactions, making it difficult to obtain multi-point synergistic binding gain comparable to that of the target triazole compound. Therefore, the selectivity of the material for triazoles will be further amplified.

[0017] In addition, intermolecular hydrogen bonds make the structure of the grafted organic layer more compact and ordered, which is conducive to maintaining the effective state of the functional units during the cycle. This provides a structural basis for the material to maintain stable adsorption and photoresponse performance, effectively improves the cycle stability of the material, and extends the cycle life of the material's photoresponse function.

[0018] Application of photoresponsive mesoporous silica materials prepared by the above method in the adsorption of triazole substances.

[0019] Furthermore, the triazole substance is tebuconazole.

[0020] The present invention has the following technical effects: This invention effectively solves the technical problems of poor selectivity, difficulty in balancing selectivity improvement and photoresponse efficiency, and uneven grafting of functional groups in existing photoresponsive adsorption materials by uniformly and adjacently grafting onto the surface of a hydroxyl-activated mesoporous silica support. This effectively improves the adsorption selectivity of the adsorption material for triazoles, significantly increases the adsorption efficiency, and achieves a maximum adsorption capacity of 123.742 mg / g. The adsorption-desorption cycle stability is also significantly improved. After 10 consecutive adsorption-desorption cycles, the reversible adsorption-desorption performance of the material remains above 90%, demonstrating excellent photo-modulated reversibility and cyclic reuse stability. Attached Figure Description

[0021] Figure 1 Infrared spectrum of the AB-TPI extract, a photoresponsive molecular intermediate prepared in Example 1.

[0022] Figure 2 Infrared spectra of the photoresponsive mesoporous silica prepared in Example 1 before and after adsorption.

[0023] Figure 3 X-ray photoelectron spectrum of the photoresponsive mesoporous silica prepared in Example 1.

[0024] Figure 4 Adsorption capacity curves of photoresponsive mesoporous silica prepared in Example 1 for different concentrations of tebuconazole.

[0025] Figure 5 Adsorption capacity curves of photoresponsive mesoporous silica prepared in Example 1 for tebuconazole at different times.

[0026] Figure 6 Adsorption performance curves of photoresponsive mesoporous silica prepared in Example 1 at different pH values.

[0027] Figure 7 Adsorption-desorption cycle curves of photoresponsive mesoporous silica prepared in Comparative Example 1 and Example 1 under different light irradiation: (a) is Comparative Example 1, (b) is Example 1.

[0028] Figure 8 Comparison of the adsorption-desorption performance of photoresponsive mesoporous silica prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 on tebuconazole. Detailed Implementation

[0029] The present invention will be specifically described below through embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.

[0030] Example 1 A method for preparing a photoresponsive mesoporous silica material includes the following steps: S1. Preparation of mesoporous oxide support (1) Hexadecyltrimethylammonium bromide (CTAB) was dissolved in a mixed solvent of sodium hydroxide aqueous solution and deionized water. The pH of the system was adjusted to 12.0 to form a homogeneous mixed solution. The solution was heated to 80°C with stirring at 500 rpm, and then tetraethyl orthosilicate (TEOS) was added. The reaction was continued for 2 h to obtain a white colloidal suspension. After the reaction was completed, the product was collected by centrifugation, washed with deionized water and methanol, and dried to obtain a mesoporous silica precursor containing a template agent. The volume ratio of sodium hydroxide solution to deionized water in the mixed solvent was 1:160, the concentration of sodium hydroxide solution was 2 mol / L, the mass ratio of CTAB to the mixed solvent was 1:480 g / mL, and the volume ratio of TEOS to the mixed solution was 1:96. (2) The mesoporous silica precursor containing the template agent was dispersed in a mixture of methanol and hydrochloric acid solution at a solid-liquid ratio of 1:100 g / mL. The mixture was refluxed at 60°C for 12 h to remove the template agent. After the reaction was completed, the solid product was collected by centrifugation and washed with methanol until neutral to obtain the mesoporous silica support MS. The volume ratio of methanol to hydrochloric acid solution was 100:1.0. The HCl concentration in the hydrochloric acid solution was 1.0 mol / L. (3) MS was dispersed in 0.5 mol / L dilute nitric acid solution with a solid-liquid ratio of 1:80 g / mL. The surface hydroxyl groups were activated by stirring and refluxing at 80℃ for 4 h. After the reaction was completed, the solid was collected by centrifugation and washed with deionized water until the filtrate was neutral. After drying, hydroxyl-activated mesoporous silica carrier MS-OH was obtained. S2. Synthesis of AB-TPI 3-(triethoxysilyl)propyl isocyanate and 4-aminoazobenzene were dissolved in anhydrous tetrahydrofuran at a solid-liquid ratio of 7:24 g / mL. The reaction was carried out under reflux at 65°C for 22 h in the dark and under nitrogen protection. After the reaction was completed, n-hexane was added and crystallized at -20°C for 10 h. The precipitated product was washed and dried under vacuum to obtain the photoresponsive molecular intermediate AB-TPI. The mass ratio of 3-(triethoxysilyl)propyl isocyanate to 4-aminoazobenzene and n-hexane was 4:3. S3. The mesoporous silica support MS-OH prepared in step S1 was dispersed in anhydrous toluene, and a mixture of AB-TPI and γ-ureapropyltriethoxysilane (UPTES) prepared in step S2 was added. The mixture was refluxed at 80°C for 12 h under light protection and nitrogen protection. After the reaction was completed, the product was collected by filtration and unreacted monomers were removed by washing with methanol. Finally, the product was vacuum dried at 60°C for 12 h to obtain the photoresponsive mesoporous silica material MS-AZO-Urea. The solid-liquid ratio of MS-OH to toluene was 1:100 g / mL. The total amount of AB-TPI and UPTES was in a mass ratio of 1:9 to MS, and the mass ratio of AB-TPI to UPTES was 1.1:1.

[0031] The infrared spectrum of the photoresponsive intermediate prepared in this embodiment is shown below. Figure 1 As shown. The infrared spectra of the adsorbent material MS-AZO-Urea before and after adsorption of tebuconazole prepared in this embodiment are as follows. Figure 2 As shown. It can be seen that 1083cm - ¹、801cm - ¹ represents the Si-O-Si stretching vibration of the SiO2 framework; 2926 cm⁻¹ - ¹、2854cm - ¹ represents the alkyl-CH2- vibration of an organosilanes; 1643 cm⁻¹ - ¹、1540cm - ¹ is the characteristic absorption of urea C=O and NH groups; 1494 cm⁻¹ - ¹、1422cm - ¹ represents the characteristic peaks of the azobenzene ring and -N=N-. After adsorption, the positions of the silica framework and the characteristic peaks of the azobenzene remain essentially unchanged; the urea group peak is at 1643 cm⁻¹. - ¹(C=O), 1540cm - ¹The (NH) absorption peak shows a shift in position and broadening in shape; simultaneously, the absorption peak at 1250–1350 cm⁻¹... - ¹、2960~2870cm - ¹ The enhanced peak shape in the region is attributed to the CN and alkyl CH absorption signals of the tebuconazole molecule. These changes indicate that tebuconazole undergoes hydrogen bonding interactions with the urea sites on the material surface, successfully adsorbing onto the material surface without disrupting the azobenzene and urea functional group framework grafted onto the material itself.

[0032] The X-ray photoelectron spectroscopy (XPS) full spectrum of the photoresponsive mesoporous silica adsorbent material prepared in this embodiment is shown in Figure 3. Characteristic signal peaks for four elements—Si, O, C, and N—can be observed in the spectrum. The signals for Si and O mainly originate from the inorganic framework of the mesoporous silica. The appearance of the characteristic peak for N indicates that the nitrogen-containing photoresponsive molecular intermediate and urea group have been successfully grafted onto the silica support. The Si2p spectrum confirms the formation of a silicon-oxygen covalent interface, jointly demonstrating that the azobenzene photoresponsive unit and the urea group recognition group are covalently grafted onto the mesoporous silica. Combined with the corresponding organic signal for C, this further proves the successful synthesis of the target photoresponsive mesoporous silica material.

[0033] MS-AZO-Urea adsorption capacity test: 10 mg of photoresponsive mesoporous silica MS-AZO-Urea and 10 mL of tebuconazole aqueous solution with initial concentrations of (10, 20, 30, 50, 100, 150 mg / L, 200 mg / L) were placed in an Erlenmeyer flask and mixed thoroughly. The flask was then sealed and placed in a constant-temperature shaker at 200 rpm. After adsorption, a portion of the solution was extracted, filtered through a 0.45 μm filter membrane, and the concentration of the remaining analyte was determined using high-performance liquid chromatography (HPLC). Adsorption curves were plotted. The adsorption curves at different initial concentrations are shown below. Figure 4 As shown, with increasing initial concentration, the equilibrium adsorption capacity of the material gradually increases and tends to saturate, with a maximum adsorption capacity reaching 123.742 mg g. -1 .

[0034] Adsorption kinetics experiments were conducted on 10 mg of the prepared photoresponsive mesoporous silica material and 10 mL of a 50 mg / L tebuconazole aqueous solution. Samples were taken at different contact time points (1, 2, 3, 5, 7, 10, 20, and 30 min) to determine the concentration of the remaining analyte in the solution. The adsorption capacity curves are shown below. Figure 5 As shown, the adsorption process exhibits distinct phased characteristics: the adsorption rate is extremely fast within the first 5 minutes of the reaction, and the adsorption amount increases rapidly; subsequently, the adsorption rate gradually slows down, and adsorption equilibrium is basically reached at around 10 minutes.

[0035] Test on the effect of pH on adsorption performance: The pH of the tebuconazole solution was adjusted to the range of 3–11 using HCl or NaOH solution. 10 mg of the prepared photoresponsive mesoporous silica was mixed with 10 ml of 50 mg / L tebuconazole aqueous solution at the corresponding pH. -1 The mixture was placed in an Erlenmeyer flask, mixed thoroughly, sealed, and then shaken at 200 rpm in a constant-temperature shaker. After adsorption was complete, a portion of the solution was extracted, filtered through a 0.45 μm filter membrane, and the concentration of the remaining analyte in the solution was determined using high-performance liquid chromatography (HPLC).

[0036] Adsorption results in the pH range of 3-11 are as follows Figure 6 As shown, the adsorption efficiency initially increases and then decreases with increasing pH. Under acidic conditions, both the adsorbent surface and the protonated tebuconazole molecules are positively charged, leading to electrostatic repulsion and low adsorption efficiency. As pH increases, electrostatic repulsion gradually weakens, and hydrophobic and hydrogen bonding interactions gradually become dominant, resulting in improved adsorption performance. Under alkaline conditions, the silanol groups on the material surface undergo deprotonation, enhancing surface hydration and weakening hydrogen bonding and hydrophobic interactions, thus reducing adsorption performance. However, the adsorption performance of the material remains above 90% at different pH levels, indicating good anti-interference properties.

[0037] Adsorption-desorption cycle stability test: 10 mg of the photoresponsive mesoporous silica prepared in Example 1 was added to 10 mL of 200 mg / L tebuconazole aqueous solution and mixed thoroughly in an Erlenmeyer flask. The flask was then sealed and placed in a constant-temperature shaker at 200 rpm for adsorption. After adsorption, a sample was taken, filtered through a 0.45 μm filter membrane, and the concentration of the remaining analyte in the solution was determined by high-performance liquid chromatography (HPLC). Subsequently, the material was desorbed and regenerated under alternating visible and ultraviolet light irradiation. This adsorption-desorption operation was repeated 10 times to evaluate the reversibility, reusability, and stability of the material's photoresponsiveness. The adsorption-desorption cycle stability of the photoresponsive mesoporous silica prepared in Comparative Example 1 was tested using the same method.

[0038] Adsorption-desorption cycle curves are as follows Figure 7 As shown in the figure (Des represents desorption, Ads represents adsorption, Vis represents visible light, and UV represents ultraviolet light), after 10 consecutive adsorption-desorption cycles, the reversible adsorption-desorption switching behavior of MS-AZO-Urea prepared in Example 1 did not change significantly, indicating that the material has excellent photo-controlled reversibility and cyclic reuse stability. In contrast, the adsorption performance of the adsorbent material prepared in Comparative Example 1 decreased after cycling, mainly due to trace mass loss during regeneration, and the photoisomerization efficiency of the azophenyl groups gradually decreased after repeated light exposure.

[0039] Comparative Example 1 Compared with Example 1, only the single AB-TPI grafting in step S2 was performed, and no further UPTES grafting was performed. The remaining steps were the same as in Example 1.

[0040] Comparative Example 2 Compared with Example 1, the AB-TPI grafting in step S2 was not performed, and the single UPTES grafting in step S3 was performed directly. The remaining steps were the same as in Example 1.

[0041] Comparative Example 3: Compared with Example 1, no hydroxyl activation treatment was performed when preparing the mesoporous dioxide support, and the subsequent steps were the same as in Example 1.

[0042] Adsorption-desorption performance tests were conducted on 10 mg of each of the materials from Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, and 10 mL of a 200 mg / L tebuconazole solution. The adsorption results are as follows: Figure 8 As shown. Under visible light irradiation, the adsorption capacity of Example 1 was the highest among all samples. After ultraviolet light irradiation, all materials exhibited varying degrees of photoinduced desorption behavior, with Example 1 showing the lowest adsorbate residue and the most outstanding phototriggered release performance.

[0043] Selective testing: (1) Single-component adsorption test: 200 mg / L solutions of tebuconazole, naphthalene, carbendazim, and 2,4-dichlorophenol were prepared respectively; 10 mg of each material from Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were taken and 10 mL of the single-component solution were added respectively, and the mixture was shaken until equilibrium was reached; the supernatant was collected by centrifugation, filtered through a membrane, and the equilibrium concentration was determined by HPLC. The single-component equilibrium adsorption capacity of each substance was calculated. The results are shown in Table 1.

[0044] Table 1:

[0045] (2) Quaternary mixed competitive adsorption test: A quaternary mixed solution of tebuconazole, naphthalene, carbendazim, and 2,4-dichlorophenol was prepared, with an initial concentration of 200 mg / L for each of the four substances; 10 mg of each of the five groups of materials was added to 10 mL of the mixed solution, and adsorption was carried out under the same conditions until equilibrium was reached; the supernatant was collected by centrifugation, and the equilibrium concentrations of the four substances were determined simultaneously by high performance liquid chromatography (HPLC). The equilibrium adsorption capacity of each substance in the mixed system was calculated. The selectivity coefficient of tebuconazole in the mixed system was calculated using the following formula: Selectivity coefficient S = Q 戊唑醇 / Q 干扰物 In the formula, Q 戊唑醇 Q represents the adsorption capacity of tebuconazole; 干扰物 The value of S represents the adsorption amount of other interfering substances. The larger the S value, the stronger the adsorption selectivity of the material for tebuconazole. The results are shown in Table 2.

[0046] Table 2:

[0047] (3) Photoresponsive desorption performance test: The photodesorption rate reflects the photoresponsive desorption performance. Photodesorption rate (i.e., photoresponsive on / off ratio) = (adsorption amount at adsorption saturation - residual adsorption amount on the material after UV irradiation) / adsorption amount at adsorption saturation × 100%. The higher the value, the more thorough the pollutant desorption after irradiation, the stronger the photocontrolled regeneration ability of the material, and the more significant the photoresponsive on / off effect. The test results are shown in Table 3.

[0048] Table 3:

[0049] Example 2 A method for preparing a photoresponsive mesoporous silica material includes the following steps: S1. Preparation of mesoporous oxide support (1) Hexadecyltrimethylammonium bromide (CTAB) was dissolved in a mixed solvent of sodium hydroxide aqueous solution and deionized water. The pH of the system was adjusted to 11.5 to form a homogeneous mixed solution. The solution was heated to 75°C with stirring at 450 rpm, and then tetraethyl orthosilicate (TEOS) was added. The reaction was continued for 2.5 h to obtain a white colloidal suspension. After the reaction was completed, the product was collected by centrifugation, washed with deionized water and methanol, and dried to obtain a mesoporous silica precursor containing a template agent. The volume ratio of sodium hydroxide solution to deionized water in the mixed solvent was 1:150, the concentration of sodium hydroxide solution was 1.5 mol / L, the mass ratio of CTAB to the mixed solvent was 1:475 g / mL, and the volume ratio of TEOS to the mixed solution was 1:95. (2) The mesoporous silica precursor containing the template agent was dispersed in a mixture of methanol and hydrochloric acid solution with a solid-liquid ratio of 1:90 g / mL. The mixture was refluxed at 55°C for 12 h to remove the template agent. After the reaction was completed, the solid product was collected by centrifugation and washed with methanol until neutral to obtain the mesoporous silica support MS. The volume ratio of methanol to hydrochloric acid solution was 100:0.8. The HCl concentration in the hydrochloric acid solution was 0.8 mol / L. (3) MS was dispersed in 0.5 mol / L dilute nitric acid solution with a solid-liquid ratio of 1:75 g / mL. The surface hydroxyl groups were activated by stirring and refluxing at 80℃ for 3.5 h. After the reaction was completed, the solid was collected by centrifugation, washed with deionized water until the filtrate was neutral, and dried to obtain hydroxyl-activated mesoporous silica support MS-OH. S2. Synthesis of AB-TPI 3-(triethoxysilyl)propyl isocyanate and 4-aminoazobenzene were dissolved in anhydrous tetrahydrofuran at a solid-liquid ratio of 7:22~26 g / mL. The reaction was carried out under reflux at 60 °C for 20~24 h in the dark and under nitrogen protection. After the reaction was completed, n-hexane was added and crystallization was carried out at -20 °C for 11 h. The precipitated product was washed and dried under vacuum to obtain the photoresponsive molecular intermediate AB-TPI. The mass ratio of 3-(triethoxysilyl)propyl isocyanate to 4-aminoazobenzene and n-hexane was 4.5:3. S3. The mesoporous silica support MS-OH prepared in step S1 was dispersed in anhydrous toluene, and a mixture of AB-TPI and γ-ureapropyltriethoxysilane (UPTES) prepared in step S2 was added. The mixture was refluxed at 75°C for 10 h under light protection and nitrogen protection. After the reaction was completed, the product was collected by filtration and unreacted monomers were removed by washing with methanol. Finally, the product was vacuum dried at 55°C for 12 h to obtain the photoresponsive mesoporous silica material MS-AZO-Urea. The solid-liquid ratio of MS-OH to toluene was 1:90 g / mL. The total amount of AB-TPI and UPTES was in a mass ratio of 1:8 to MS, and the mass ratio of AB-TPI to UPTES was 1:1.

[0050] The photoresponsive mesoporous silica material MS-AZO-Urea prepared in this embodiment has a maximum adsorption capacity of 121.472 mg / g for tebuconazole. After 10 consecutive adsorption-desorption cycles, the adsorption performance remains above 90%.

[0051] Example 3 A method for preparing a photoresponsive mesoporous silica material includes the following steps: S1. Preparation of mesoporous oxide support (1) Hexadecyltrimethylammonium bromide (CTAB) was dissolved in a mixed solvent of sodium hydroxide aqueous solution and deionized water. The pH of the system was adjusted to 12.5 to form a homogeneous mixed solution. The solution was heated to 85°C with stirring at 550 rpm, and then tetraethyl orthosilicate (TEOS) was added. The reaction was continued for 1.5 h to obtain a white colloidal suspension. After the reaction was completed, the product was collected by centrifugation, washed with deionized water and methanol, and dried to obtain a mesoporous silica precursor containing a template agent. The volume ratio of sodium hydroxide solution to deionized water in the mixed solvent was 1:155, the concentration of sodium hydroxide solution was 2.5 mol / L, the mass ratio of CTAB to the mixed solvent was 1:485 g / mL, and the volume ratio of TEOS to the mixed solution was 1:98. (2) The mesoporous silica precursor containing the template agent was dispersed in a mixture of methanol and hydrochloric acid solution at a solid-liquid ratio of 1:100 g / mL. The mixture was refluxed at 68°C for 10 h to remove the template agent. After the reaction was completed, the solid product was collected by centrifugation and washed with methanol until neutral to obtain the mesoporous silica support MS. The volume ratio of methanol to hydrochloric acid solution was 100:1.2. The HCl concentration in the hydrochloric acid solution was 1.2 mol / L. (3) MS was dispersed in 0.5 mol / L dilute nitric acid solution with a solid-liquid ratio of 1:85 g / mL. The surface hydroxyl groups were activated by stirring and refluxing at 80℃ for 4.5 h. After the reaction was completed, the solid was collected by centrifugation, washed with deionized water until the filtrate was neutral, and dried to obtain hydroxyl-activated mesoporous silica carrier MS-OH. S2. Synthesis of AB-TPI 3-(triethoxysilyl)propyl isocyanate and 4-aminoazobenzene were dissolved in anhydrous tetrahydrofuran at a solid-liquid ratio of 7:26 g / mL. The reaction was carried out under reflux at 68 °C for 24 h in the dark and under nitrogen protection. After the reaction was completed, n-hexane was added and crystallized at -20 °C for 12 h. The precipitated product was washed and dried under vacuum to obtain the photoresponsive molecular intermediate AB-TPI. The mass ratio of 3-(triethoxysilyl)propyl isocyanate to 4-aminoazobenzene and n-hexane was 5:3. S3. The mesoporous silica support MS-OH prepared in step S1 was dispersed in anhydrous toluene, and a mixture of AB-TPI and γ-ureapropyltriethoxysilane (UPTES) prepared in step S2 was added. The mixture was refluxed at 85°C for 10 h under light protection and nitrogen protection. After the reaction was completed, the product was collected by filtration and unreacted monomers were removed by washing with methanol. Finally, the product was vacuum dried at 65°C for 12 h to obtain the photoresponsive mesoporous silica material MS-AZO-Urea. The solid-liquid ratio of MS-OH to toluene was 1:100 g / mL; the total amount of AB-TPI and UPTES was in a mass ratio of 1:10 to MS, and the mass ratio of AB-TPI to UPTES was 1.2:1.

[0052] The photoresponsive mesoporous silica material MS-AZO-Urea prepared in this embodiment has a maximum adsorption capacity of 122.316 mg / g for tebuconazole. After 10 consecutive adsorption-desorption cycles, the adsorption performance remains above 90%.

Claims

1. A method for preparing a photoresponsive mesoporous silica adsorbent material, characterized in that, Includes the following steps: S1. Mesoporous silica MS was prepared by sol-gel method using hexadecyltrimethylammonium bromide (CTAB) as template, and MS-OH was obtained by hydroxyl activation. S2. The photoresponsive molecular intermediate AB-TPI was synthesized by reacting 3-(triethoxysilyl)propyl isocyanate and 4-aminoazobenzene. S3. MS-OH, AB-TPI and γ-ureapropyltriethoxysilane UPTES are mixed and reacted to obtain the photoresponsive mesoporous silica adsorbent material MS-AZO-Urea.

2. The method for preparing a photoresponsive mesoporous silica adsorbent material as described in claim 1, characterized in that: The preparation of mesoporous silica involves dissolving hexadecyltrimethylammonium bromide (CTAB) in a mixed solvent of sodium hydroxide aqueous solution and deionized water, adjusting the pH of the system to 11.5–12.5 to form a homogeneous mixed solution, then adding tetraethyl orthosilicate (TEOS), and reacting for 1.5–2.5 hours to obtain a white colloidal suspension. After the reaction, the product is collected by centrifugation, washed with deionized water and methanol, and dried to obtain a mesoporous silica precursor containing a template agent. The mesoporous silica precursor containing the template agent is dispersed in a mixed system of methanol and hydrochloric acid solution, and refluxed to remove the template agent. After the reaction, the solid product is collected by centrifugation and washed until neutral to obtain the mesoporous silica support MS.

3. The method for preparing a photoresponsive mesoporous silica adsorbent material as described in claim 2, characterized in that: The volume ratio of sodium hydroxide solution to deionized water in the mixed solvent is 1:150~160, the concentration of sodium hydroxide solution is 1.5~2.5mol / L, the mass ratio of CTAB to the mixed solvent is 1:475~485 g / mL, and the volume ratio of TEOS to the mixed solution is 1:95~98.

4. A method for preparing a photoresponsive mesoporous silica adsorbent material as described in claim 2 or 3, characterized in that: The reflux reaction is carried out at a temperature of 55-65°C for 10-12 hours, and the volume ratio of methanol to hydrochloric acid solution is 100:0.8-1.

2. The concentration of HCl in the hydrochloric acid solution is 0.8-1.2 mol / L.

5. A method for preparing a photoresponsive mesoporous silica adsorbent material as described in claim 4, characterized in that: The hydroxyl activation involves dispersing MS in a dilute nitric acid solution for activation. After the reaction is complete, the solid is collected by centrifugation, washed with deionized water until the filtrate is neutral, and dried to obtain hydroxyl-activated mesoporous silica carrier MS-OH.

6. The method for preparing a photoresponsive mesoporous silica adsorbent material as described in claim 5, characterized in that: The activation reaction was carried out at a temperature of 75-85℃ for 3.5-4.5 h, with a concentration of 0.5 mol / L for dilute nitric acid and a solid-liquid ratio of MS to dilute nitric acid of 1:75-85 g / mL.

7. The method for preparing a photoresponsive mesoporous silica adsorbent material as described in claim 6, characterized in that: The photoresponsive molecular intermediate AB-TPI was synthesized by dissolving 3-(triethoxysilyl)propyl isocyanate and 4-aminoazobenzene in anhydrous tetrahydrofuran at a solid-liquid ratio of 7:22~26 g / mL, and refluxing at 60~68℃ for 20~24 h under light-protected and nitrogen-protected conditions. After the reaction was completed, hexane was added and crystallized at -20℃ for 10~12 h. The precipitated product was washed and dried under vacuum to obtain the photoresponsive molecular intermediate AB-TPI.

8. The method for preparing a photoresponsive mesoporous silica adsorbent material as described in claim 7, characterized in that: The mixed reaction involves dispersing hydroxyl-activated mesoporous silica MS-OH in anhydrous toluene, adding a mixture of AB-TPI and γ-ureapropyltriethoxysilane UPTES, and refluxing at 75-85°C for 10-12 h under light-protected and nitrogen-protected conditions. After the reaction, the product is collected by filtration, and unreacted monomers are removed by washing with methanol. Finally, the product is vacuum-dried at 55-65°C for 12 h to obtain the photoresponsive mesoporous silica adsorbent material MS-AZO-Urea.

9. The application of the photoresponsive mesoporous silica adsorbent material prepared by the method as described in claim 8 in the adsorption of triazole substances.

10. The application as described in claim 9, characterized in that: The triazole substance is tebuconazole.